Peningkatan Kemampuan Berpikir Kritis Siswa pada Materi Bangun Ruang Menggunakan Model Project Based Learning (PjBL) di Kelas V SD - Mashal Hadi; Sabahiyah Sabahiyah; Muhamad Akrom; Junaidi Junaidi; Ihwan Ihwan; Siti Raesah Ayu (Journal of Teaching and Elementary Education, 2026)
Students’ mathematical critical thinking skills in Indonesia remain relatively low, as reflected in the results of the 2018 PISA assessment. One of the main contributing factors is conventional teacher-centered learning. This study aims to describe the improvement of students’ critical thinking skills on the topic of three-dimensional shapes (cubes and rectangular prisms) through the implementation of the Project Based Learning (PjBL) model in Grade V of SD Negeri 01 Mamben Daya. This research is a Classroom Action Research (CAR) based on the Kemmis & Taggart model, conducted in two cycles. The research subjects consisted of 32 students (21 males and 11 females). Data were collected through a written essay test comprising five questions designed to measure indicators of interpretation, analysis, evaluation, and inference. Data analysis employed descriptive percentage techniques. The results showed a significant improvement. In the pre-cycle stage, the percentage of classical mastery of students’ critical thinking skills was only 3.12% (categorized as low). After implementing PjBL in Cycle I, the percentage increased to 56.25% (categorized as moderately critical). In Cycle II, it further increased to 78.12% (categorized as critical), exceeding the predetermined success indicator (?75%). The implementation of the Project Based Learning (PjBL) model is effective in improving the critical thinking skills of Grade V students on the concept of three-dimensional shapes. This study is recommended as an alternative instructional model to enhance the quality of mathematics learning in elementary schools.